The effects of submergence on selected Malaysian rice varieties - Noor Liyana Sukiran,; Muhammad Aiman Hafiz Jaya Karso,; Qatrunnada Qurratu’aini Mohd Razemin,; Noraziyah Abd Aziz Shamsuddin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Various varieties have been developed in Malaysia, mainly to improve rice response to environmental changes, pests, and diseases, as well as to increase rice productivity under stressful conditions. Despite being semi-aquatic plants, rice is intolerant to complete submergence for a long period. This study was conducted to evaluate the response of seven Malaysian rice varieties at the vegetative stage under submergence stress. Two-week-old rice seedlings were submerged for 14 days, and the changes in plant height, chlorophyll content, and soluble sugar content were determined. The survival percentage of these varieties was observed after 14 days of de-submergence, where UKMRC2 and MR220CL possessed high survivability (90% & 60%, respectively). After submergence, all varieties showed height increment and reduced chlorophyll and soluble sugar contents. Based on our analyses, UKMRC2 performed better than other varieties, although slightly less than IR64-Sub1. It was confirmed that UKMRC2 is the submergence-tolerant variety, and its response to underwater germination was also determined. Our result showed that UKMRC2 might possess tolerance to anaerobic germination conditions, and more studies are needed to understand its molecular mechanism for submergence. In conclusion, many varieties used were susceptible to submergence, and the development of more submergence-tolerant varieties is crucial for Malaysia’s food security sustainability.